praticas de atividade física em agentes comunitário de saúde do município de Coari, amazonas - Silva, Divino carlos (Brasil, 2024)
Abstract Objective: This study aimed to assess the level of physical activity among Community Health Agents (CHAs) in the city of Coari, Amazonas, and to understand the differences between moderate and vigorous physical activities practiced by men and women. Methodology: A quantitative approach was used, applying the short version of the International Physical Activity Questionnaire (IPAQ) to 223 CHAs. Results: The sample was predominantly female (65.9%), brown (91.5%), with complete high school education (63.2%), living with a partner (78.7%) and with children (91%). CHAs engage more in walking than in moderate or vigorous physical activities, with women surpassing men in frequency and duration of walking and moderate activities. In contrast, men showed greater dedication to vigorous activities. All participants were classified as physically active, exceeding the minimum recommendations for physical activity for health. However, the research highlighted the high amount of time spent sitting by both sexes. Conclusion: Despite the high rate of physical activity among the CHAs in Coari, the gender differences in physical activity preferences and the significant time spent in a sedentary position highlight the need for specific public policies. These policies should aim to promote an even more active lifestyle, considering the particularities of gender, socioeconomic conditions and the environment, in order to effectively reduce sedentary lifestyles and promote the comprehensive health of the CHAs.